2009
DOI: 10.1111/j.1471-0528.2009.02120.x
|View full text |Cite
|
Sign up to set email alerts
|

Women’s views on the use of decision aids for decision making about the method of delivery following a previous caesarean section: qualitative interview study

Abstract: Objective To obtain the views of women on their experiences of decision making about the method of delivery following a previous caesarean section and the role of decision aids in this process.Design Qualitative study nested within a randomised controlled trial, using repeat semi-structured interviews conducted pre-and postnatally. Data were analysed using a framework approach.Setting Three maternity units in south-west England and Scotland.Sample Purposive sample of 30 women participating in a randomised cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
60
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 19 publications
6
60
2
Order By: Relevance
“…It is known that women's decision making about mode of delivery may be influenced by cultural norms, family situation and the way risk information is presented to them by clinicians 31 32…”
Section: Resultsmentioning
confidence: 99%
“…It is known that women's decision making about mode of delivery may be influenced by cultural norms, family situation and the way risk information is presented to them by clinicians 31 32…”
Section: Resultsmentioning
confidence: 99%
“…Bredin et al 41 looked at risk related to physical activity in pregnant women and suggested using a decision tree; this approach may be a useful tool to develop for acupuncture in the context of pregnancy. 42 These tools may, without being alarmist or protectionist, enable practitioners to ensure that patients are fully informed about intervention risks and benefits, and thereby satisfy personal ethical concerns 43 and allow them to be more confident in their decision making.…”
mentioning
confidence: 99%
“…Semistructured interviews will also be conducted with a sample of 30 participants across trial arms and research sites, after participation in the trial has been completed and in order to examine aspects of intervention and participants’ experiences of diabetes consultations in more depth 48. With the participants’ consent, these interviews will be audio-recorded and will explore: participants’ experience of diabetes and clinical consultations; raising concerns with health professionals in primary and secondary care; participants’ experience of either usual care or intervention and trial participation.…”
Section: Methodsmentioning
confidence: 99%